Respons Anatomis dan Fisiologis Tanaman Kacang Tanah (Arachis hypogaea L.) terhadap Aplikasi Gibberellic Acid (GA3) dan Sludge Biogas - Harahap, Hamdian Noor; Maryani, Maryani; Yustinadiar, Novita (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Peanut production showed a positive growth but had not been able to meet the community demands. The low productivity could be solved by providing a plant growth regulators, such as GA3, and fertilizer, such as biogas sludge. The purpose of this study was to determine the anatomical and physiological responses of peanuts to the application of GA3 and biogas sludge. The research was conducted with a 4 x 2 factorial randomized block design, four levels of GA3 dose consisting of control, 50 ppm, 100 ppm, 150 ppm, and two levels of biogas sludge dose consisting of control and 70 ml / liter of water, with three repetitions so that there are 24 units. Data were analyzed statistically by Anova test followed by the DMRT test with a significance level of 95% (α = 0.05). The results showed that there were significant differences between plant anatomical responses: metaxilem diameter (p-value = 0.006), cortical thickness (p-value = 0.001) and pith diameter (p-value = 0.021), also between physiological responses: plant height (p-value = 0,000), leaf length (p-value = 0,000) and leaf width (p-value = 0.046), of peanuts applied a combination of GA3 and biogas sludges in various concentrations. On the other hand, there was no significant difference in stem diameter (p-value = 0.117), root volume (p-value = 0.650) and number of leaflets (p-value = 0.120), that were applied a combination of GA3 application and biogas sludges in various concentrations.